Nilai-Nilai Pendidikan Anak dalam Hadis Tarbawi: Analisis Tematik dan Relevansinya terhadap Pendidikan Islam Kontemporer - Nia Ramah; Dewi Indrawati (Jurnal Pendidikan Sosial Dan Konseling, 2026)
Child education in Islam is an endeavor to shape a generation characterized by faith, piety, and noble character, grounded in the teachings of the Qur'an and Hadith. As a fundamental source of Islamic teachings, hadith tarbawi (hadiths concerning education) encompasses various principles that serve as guidelines for the processes of educating and nurturing children's character. This study aims to analyze the educational values ​​for children found in hadith tarbawi using a thematic (maudhu'i) approach. It employs a library research methodology, utilizing collections of hadiths, books, and scholarly journals as data sources. The data were analyzed using a descriptive-analytical method to identify and interpret the educational values ​​contained within the hadiths. The findings indicate that hadith tarbawi embodies educational values ​​such as faith, acts of worship, moral character, compassion, responsibility, and exemplary conduct. These values ​​remain relevant as a foundation for Islamic education in shaping children's character in the modern era. Consequently, the application of the values ​​found in hadith tarbawi is expected to strengthen character development and foster a Muslim generation possessing noble character and an Islamic identity, capable of navigating the challenges of the changing times.